Bioactivity and Apoptotic Efficacy of the Purified Terpenoid Extract from the Moss Brachythecium Buchananii (Hook.) A. Jaeger against MG 63 Cells (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Bryophytes are primitive non vascular plants. A little is explored regarding the medicinal effects of bryophytes on carcinoma. This study investigated the biological effects of purified terpenoids from Brachythecium buchananii on selected cell lines such as HeLa, MDAMB-231 and MG63 human osteosarcoma cells and also elucidating the regulatory signaling pathways underlying the effects of terpenoids towards caspase cascade and the antioxidant enzyme system. The cell lines were treated with various concentrations of purified terpenoid extracts interms of evaluating viability (MTT assay). Interestingly, MG63 cell lines showed poor viability as compared to other ongo cells and was subjected to further molecular evaluations. Migration and invasion assay results using wound-healing and transwell assays, respectively reveal the pro-antimetastatic potential of the purified terpenoids from the moss. The flow cytometry study substantiated terpenoid induced apoptosis in MG63 cells. Cell cycle analysis revealed the significant increase in the number of cells arrested at the S growth phase. Terpenoid extract also displayed DNA fragmentation in the cells. Western blot analysis revealed the down regulation of the anti‑apoptotic proteins Bcl‑2, pro‑caspase 3 and over expression of the pro‑apoptotic protein Bax. In addition, the caspase cascade profile of the terpenoid extract substantiated their efficacy in tumour inhibition. Thus, the overall results confirmed the biological features of terpenoid induced apoptosis in the MG63 cells.